Semi-formal Analysis of the Formality-Informality Opposition in the Spirit of the Lvov-Warsaw School - Jadacki, Jacek (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
The starting point of this paper is conceptual-terminological specifica[1]tion within the class of transformations performed on language formulas. The following types of transformations are distinguished: enlargement, generalization, extrapolation and variabilization – as well as standardization, schematization and clarification. The term “formalization” is sometimes used as a synonym for “variabilization”, “schematization” (that is, in the basic sense basic sense), or “axiomatization.” Each theory is inherently a formal theory (in the basic sense); therefore, the opposition of formal theories to informal theories, and in particular of formal logic to informal logic, has no reason for existence; instead of the formality vel informality of some theories, e.g. logic, one should say that one theory, in particular a logical theory, is more (or less) formal than another. The motive for postulating informal logic is the charge of inadequacy against traditional formal logic. In fact, what is practiced under the banner of “informal logic” is sometimes the result of operations that have been called “clarification” here, or such an extension of classical logic that would be a theory of argumentation more adequate than the latter. Tekst powstał w ramach projektu 2015/18/E/HS1/00478 „Filozofia z metodologicznego punktu widzenia. Kondycja i perspektywy dyscyplin filozoficznych w świetle paradygmatu Szkoły Lwowsko-Warszawskiej” finansowanego przez Narodowe Centrum Nauki.